Phytosanitary management of arthropds in the vineyards in Bandeirantes and Marialva, north of Paraná state, Brazil - Rando, Jael Simões Santos; Piovesani, Marina Dias; de Oliveira, Natália Rocon; Falleiros, Fernanda Thaísa dos Santos; Schauff, Lucas Oliveira; Matsuyama, Simone dos Santos (Scientia Agraria Paranaensis, 2017)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false PT-BR JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> <span style="font-family: 'Helvetica',sans-serif; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The production of fine grapes in the state of Paraná is mainly concentrated in the North. In this work we carried out the diagnosis of control disease and insect pest mites through a questionnaire covering 10% of grape growers in the municipalities of Bandeirantes and 5% Marialva. The issues involved socio-economic, technical, faced problems due to the attack of insects and mites and control strategies adopted by producers. The major arthropod pests in the region are caterpillar-of-curls, thrips, mealybugs and mites. The control carried out principally through the application of insecticides and miticides neonicotinoid imidacloprid, the pyrethroids zeta-cypermethrin and bifenthrin and the avermectin abamectin. It is essential that technical and diffusers of agricultural sciences guide the grape growers in the search and adoption of other forms of insect and mites control and the use of insecticides in order to add value to production. <!--EndFragment-->